If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 50 = 4x Reorder the terms: 50 + X = 4x Solving 50 + X = 4x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-50' to each side of the equation. 50 + -50 + X = -50 + 4x Combine like terms: 50 + -50 = 0 0 + X = -50 + 4x X = -50 + 4x Simplifying X = -50 + 4x
| X+5x=4x | | 100x-10x=10 | | 500+ap=5000 | | 4d+3=-16d | | 4-2b=19 | | 5x-4x+3=x | | 747-60x=300 | | 5(z+2)=25 | | 7-3x=y | | 2345x-23167=3 | | 747-60x=147 | | 25z+5-8=147 | | 0.4-1.2=0.3r+0.6 | | 8q=32 | | 7(-2x+10)=42 | | 8(2-5x)=-264 | | 11.3+-7.2=3.82 | | 747-60x=0 | | 4y+5(5+y)=-2 | | ax+by=0 | | 2(-4r+2)=-6(-8+2r) | | .53y+2.5=5.1 | | -88+9z=z | | 3xz+4-8=1 | | 2(4d+5h)-(9h-5d)= | | 2x+1+4x+4=4 | | 7u-22=-1 | | -8(6x+5)=-520 | | 4h+7=4h | | x+3=30 | | 220+0.15x=368.50 | | (3x^2y+7xy^2)(x^2y^3-2y^2)= |